Energetics and stability of nanostructured amorphous carbon - Fyta, Maria G.; Remediakis, Ioannis N.; Kelires, Pantelis C. (My University, 2003)
Monte Carlo simulations, supplemented by ab initio calculations, shed light onto the energetics and thermodynamic stability of nanostructured amorphous carbon. The interaction of the embedded nanocrystals with the host amorphous matrix is shown to determine in a large degree the stability and the relative energy differences among carbon phases. Diamonds are stable structures in matrices with sp3 fraction over 60%. Schwarzites are stable in low-coordinated networks. Other sp2-bonded structures are metastable.
Keywords: Carbon; Thermodynamics; Chemical structure; Energy transfer